The Role of Narratives of King Taksin the Great Towards People in Rayong Province - Jareanwai, Nuchalak; Srichanthawong, Payungporn; Nunphooban, Suratadchanukoon (Mahachula Academic Journal, 2025)
This academic article aims to present the role of the narrative of King Taksin the Great towards the people of Rayong Province. The data was collected from documents, field data, and social media through interviews with local scholars, monks, cultural academics, and villagers from the Wat Lum Mahachai Chumphon community in Tha Pradu Sub-district, Mueang Rayong District, Rayong Province, totaling 10 informants. The participatory observation was implemented in traditions, rituals, and beliefs related to King Taksin the Great. The analysis and interpretation were conducted using the concept of narratives and the theories of functional roles in folklore" The study revealed that the narratives about King Taksin the Great are connected with national history and local history. The people of Rayong Province believe that King Taksin the Great camped at the area of Wat Lum Mahachai Chumphon, where he tethered his royal elephant named ’Pangkhiri Banchorn’ while stating his intention among the meeting with the local leaders and residents of Rayong to reclaim independence from the Burmese. The people of Rayong united in support of King Taksin as their military leader, launching an attack on Chanthaburi, gathering troops to recover Ayutthaya by sea. From these narratives, there are six roles identified for the people of Rayong: (1) being a mental anchor (2) creating community and provincial identity; (3) fostering creative traditions; (4) promoting historical consciousness, patriotism, and unity; (5) forming ethnic consciousness; and (6) developing tourist attractions and learning centers.